2014
DOI: 10.1016/j.actamat.2014.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale analysis of liquid-gallium embrittlement of aluminum grain boundaries

Abstract: Material strengthening and embrittlement are controlled by intrinsic interactions between defects, such as grain boundaries (GB), and impurity atoms that alter the observed deformation and failure mechanisms in metals. In this work, we explore the role of atomistic-scale energetics on liquid-metal embrittlement of aluminum (Al) due to gallium (Ga). Ab initio and molecular mechanics were employed to probe the formation/binding energies of vacancies and segregation energies of Ga for <100>, <110> and <111> symme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(43 citation statements)
references
References 78 publications
2
41
0
Order By: Relevance
“…Yang et al [10] and Palafox-Hernandez et al [11] detailedly characterized the Al-Pb and Cu-Pb solid-liquid interface, respectively, by the density, potential energy, stress and diffusion constant profiles, as well as the two-dimensional Fourier analysis of the interfacial layers. Nam et al [4] and Rajagopalan et al [5] examined the liquid metal embrittlement of the Al-Ga system, and Nam's results agree well with both the dislocation-climb model and general trends gleaned from the experimental studies. Hashibon et al [12] created interatomic potentials for Ta-Cu system and the dewetting phenomenon of liquid Cu on Ta substrate was observed in their simulation.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Yang et al [10] and Palafox-Hernandez et al [11] detailedly characterized the Al-Pb and Cu-Pb solid-liquid interface, respectively, by the density, potential energy, stress and diffusion constant profiles, as well as the two-dimensional Fourier analysis of the interfacial layers. Nam et al [4] and Rajagopalan et al [5] examined the liquid metal embrittlement of the Al-Ga system, and Nam's results agree well with both the dislocation-climb model and general trends gleaned from the experimental studies. Hashibon et al [12] created interatomic potentials for Ta-Cu system and the dewetting phenomenon of liquid Cu on Ta substrate was observed in their simulation.…”
Section: Introductionsupporting
confidence: 75%
“…According to the constituent materials we can divide them into two classes: homogeneous solid-liquid interfaces and heterogeneous solid-liquid interfaces, and the latter exist more widely. Solid-liquid interfaces play important roles in engineering ranging from solidification, melting, corrosion, to liquid metal embrittlement and so on [1][2][3][4][5][6]. Therefore they have attracted a longstanding interest from scientists and technologists, however we still know little about them for their intrinsic complexity and the limitation of M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT experimental condition.…”
Section: Introductionmentioning
confidence: 99%
“…The periodic boundaries were maintained with a separation distance of 25 nm between the boundaries. Several 0 K minimum energy GB structures were obtained through successive rigid body translations followed by an atom deletion technique and energy minimization using a nonlinear conjugate method [24,[28][29][30][37][38][39]. In particular, grain boundary structures generated using this technique have been compared with experimental high-resolution transmission electron microscopy images [65][66][67].…”
Section: Equilibrium Grain Boundary Structuresmentioning
confidence: 99%
“…Furthermore, onset of plastic deformation is complicated due to the dissociated and faceted structure present in GB interfaces [23,24]. Hence, the local structure and character of the Research has shown that GB properties are affected by both the macroscopic degrees of freedom and the microscopic local structure [25][26][27][28][29][30]. The term GB character is often used to refer to the macroscopic GB degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%
“…As with past work [59][60][61][62][63][64][65][66][67] and others [68][69][70], an atom deletion criterion, multiple initial configurations, and various in-plane rigid body translations were utilized to accurately obtain an optimal minimum energy GB structure via the nonlinear conjugate gradient energy minimization process. Further details on the GB generation technique and GB structures of HCP materials are given in Bhatia and Solanki [59], and Wang and Beyerlein [71].…”
Section: Grain Boundary Slidingmentioning
confidence: 99%